Overcoming the Challenges of Detecting GPCR Oligomerization in the Brain - Fernández-Dueñas, Víctor; Bonaventura, Jordi; Aso, Ester; Luján, Rafael; Ferré, Sergi; Ciruela, Francisco (Current Neuropharmacology, 2022)
G protein-coupled receptors (GPCRs) constitute the largest group of membrane receptor proteins controlling brain activity. Accordingly, GPCRs are the main target of commercial drugs for most neurological and neuropsychiatric disorders. One of the mechanisms by which GPCRs regulate neuronal function is by homo- and heteromerization, with the establishment of direct protein-protein interactions between the same and different GPCRs. The occurrence of GPCR homo- and heteromers in artificial systems is generally well accepted, but more specific methods are necessary to address GPCR oligomerization in the brain. Here, we revise some of the techniques that have mostly contributed to reveal GPCR oligomers in native tissue, which include immunogold electron microscopy, proximity ligation assay (PLA), resonance energy transfer (RET) between fluorescent ligands and the Amplified Luminescent Proximity Homogeneous Assay (ALPHA). Of note, we use the archetypical GPCR oligomer, the adenosine A2A receptor (A2AR)-dopamine D2 receptor (D2R) heteromer as an example to illustrate the implementation of these techniques, which can allow visualizing GPCR oligomers in the human brain under normal and pathological conditions. Indeed, GPCR oligomerization may be involved in the pathophysiology of neurological and neuropsychiatric disorders.
Keywords: TR-FRET